Challenges and Opportunities of Green Energy Adoption in Global Economic Development - Qianyue, Cai (Journal of Environmental Economics and Sustainability, 2025)
The transition to green energy is a critical component of sustainable global economic development. This paper examines the challenges and opportunities associated with the adoption of green energy technologies worldwide. It highlights the economic, environmental, and social benefits of green energy while addressing the barriers such as high initial costs, technological limitations, and policy inconsistencies. The study uses a combination of qualitative and quantitative data to analyze the current of state green energy adoption and future prospects. The findings suggest that while significant challenges remain, the opportunities for economic growth, job creation, and environmental sustainability are substantial. The paper concludes that a coordinated global effort, supported by robust policies and investment, is essential to fully realize the potential of green energy in the global economy.